PENGARUH PENYULUHAN PERTANIAN TERHADAP EFEKTIVITAS KELOMPOK TANI JAYA DI DESA DANAR KECAMATAN KEI-KECIL TIMUR SELATAN KABUPATEN MALUKU TENGGARA - Ngabalin, Lili Suryani; Sangadji, Suwandi S.; Suhardi, Suhardi (Aksara Public, 2019)
Agricultural extension is a way to increase farmers' knowledge so that the achievement of the effectiveness of farmer groups in managing agriculture properly and correctly, this research was conducted from October to November 2018 in Danar Village, South East Kei Sub-District, Southeast Maluku Regency, the sample was 30 people / farmers the data used are primary data and secondary data and analysis using validity analysis, reliability of the correlation coefficient and determination, simple linear regression and hypothesis. The results of the analysis show that agricultural review with the effectiveness of the wealthy farmer group in good value, the results of t test calculation at the level obtained tcount> t table is 0.502> 0.361 then H0 is rejected Ha accepted, so the null hypothesis (H0) states that there is no influence of agricultural extension against the effectiveness of farmer groups rejected, while the alternative hypothesis (Ha) which states the influence of agricultural counseling on the effectiveness variable of the successful farmer group is received, the results of simple linear regression analysis equation persamaan = 4.291 + 0.682. X of the equation is known to be a regression regression of agricultural extension has a positive sign, by looking at the correlation efficiency of 0.682. This value is included in the category of low relationships, and the terminated confirmation results (r square) 0.465 or 5% and epsilon is 69% is the role given by other factors not examined in this study.